(untitled) (Law and world, 2018)
Today, in the period of free market economy, material values, including needs, are of great importance for a human’s well-being and development. Therefore, it necessitates the protection/provision of these values (needs). Pledge holds one of the first places in law which ensures needs. As pledge exists on real objects, it protects the creditor from the debtor’s insolvency. For this reason, it represents the creditor’s object of interest. In order to ensure the creditor’s needs, it would be appropriate to select valuable property.